2003
DOI: 10.3748/wjg.v9.i8.1856
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of hepatic angiomyolipoma in 26 cases

Abstract: Preoperative radiological diagnosis of HAML is possible. The demonstration of intratumoral fat and central vessels is helpful in the diagnosis. HMB45, A103 and SMA are promising markers for pathologic diagnosis of HAML, and surgical resection is effective for the treatment of HAML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 14 publications
4
60
1
1
Order By: Relevance
“…2B tumor. Recently, Ren et al reported that MRI showed hypointensity or hyperintensity on T1-weighted images and heterogeneous hyperintensity on T2-weighted images [14]. In our case, MRI clearly demonstrated a tumor in the subcutaneous region with low signal intensities and well enhanced on T1-weighted images and high signal intensities on T2-weighted images.…”
Section: Discussionsupporting
confidence: 47%
“…2B tumor. Recently, Ren et al reported that MRI showed hypointensity or hyperintensity on T1-weighted images and heterogeneous hyperintensity on T2-weighted images [14]. In our case, MRI clearly demonstrated a tumor in the subcutaneous region with low signal intensities and well enhanced on T1-weighted images and high signal intensities on T2-weighted images.…”
Section: Discussionsupporting
confidence: 47%
“…The advent of the second-generation ultrasound contrast agents and contrast-specific ultrasound techniques allows depiction of the micro-and macrocirculation of FLLs, which has facilitated a great improvement in the characterisation of FLLs [5,6]. However, until now, few reports in the literature have described the use of contrast-enhanced ultrasound (CEUS) in hepatic AML [7][8][9][10][11]. Herein we analyse retrospectively the imaging features of 12 hepatic AMLs on CEUS; the diagnostic results of BUS and CEUS before pathological examination are also recorded.…”
mentioning
confidence: 99%
“…In the present patient, hepatic EAML showed homogeneous and significantly lower signal intensity at the hepatobiliary phase at 30 min post-Gd-EOB-DTPA injection compared with the normal liver parenchyma. This may be due to the fact that EAML is mainly composed of diffused epithelioid cells with diverse morphologies, containing an abundant sinusoidal vascular network, but lacking normal liver cells; therefore, the rate of the uptake of Gd-EOB-DTPA is lower (8,9). The hepatic EAML in the current study showed a high signal intensity on DWI scans, with a higher ADC value than that of the surrounding normal liver parenchyma.…”
Section: Discussionmentioning
confidence: 74%
“…Patients with hepatic EAML usually have no specific clinical manifestations or physical signs, although with an increase in tumor size, certain patients may exhibit symptoms caused by tumor compression; however, results of all the laboratory examinations are usually negative. The diagnosis of EAML depends on the immunohistochemical examination (9), and the characteristic immunophenotype is dual positive for the expression of melanoma cells and smooth muscle cells, while the epithelial cell marker is negative. HMB45, one of the melanocytic markers, is the most sensitive marker, and SMA is the major marker for smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%